Implementing Lymphatic Mapping With Sentinel Node Biopsi in The Management of Patients with Breast Cancer - Omgo E Nieweg (Indonesian Journal of Cancer, 2007)
The past decade has brought major advances in the knowledge about breast cancer. The understanding of the underlying mechanisms of the disease has been increased by molecular biology and this field appears on the brink of becoming part of routine clinical management. The ability to diagnose the disease has been refined. New drugs have been introduced and really improve survival. If one wonders what the most significant recent advance is in the surgical management, then the author submits that lymphatic mapping is it, although he admits maybe being somewhat biased.